1999
DOI: 10.1016/s0741-5214(99)70309-5
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic aortofemoral bypass grafting: Human cadaveric and initial clinical experiences

Abstract: Laparoscopic vascular surgery seems to be a promising procedure to minimize postoperative complications. On the basis of our experience, we do not favor the TARA. Because it necessitates steep Trendelenburg positioning to displace intra-abdominal organs, the TARA is not an appropriate approach, particularly in obese and cardiopulmonary frail cases. Contrarily, the TAPA and the EPA deliver potentially better results in terms of exposing the operative field and thus reducing operating time and perioperative morb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
8

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 23 publications
0
23
0
8
Order By: Relevance
“…The authors found that cadavers were an excellent model for this study as the effectiveness of each procedure could be assessed through autopsy (Milsom et al, 1994). Another group looked at the effectiveness of laparoscopic aorto-femoral bypass grafting, using cadavers to determine the efficacy of different approaches before using the procedure on patients (Said et al, 1999). These studies show the usefulness of cadavers as a model in developing and trialing new surgical skills without exposing patients to unnecessary risks.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…The authors found that cadavers were an excellent model for this study as the effectiveness of each procedure could be assessed through autopsy (Milsom et al, 1994). Another group looked at the effectiveness of laparoscopic aorto-femoral bypass grafting, using cadavers to determine the efficacy of different approaches before using the procedure on patients (Said et al, 1999). These studies show the usefulness of cadavers as a model in developing and trialing new surgical skills without exposing patients to unnecessary risks.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…However, Said et al [19] reported that the transabdominal retroperitoneal approach caused a burdensome sliding of the intestine into the operative field, particularly in obese patients. In their experience, the transabdominal left paracolic approach retained the intestine in the upper abdomen throughout the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…In order to reduce the consequences of large incisions, many authors have suggested performing video-assisted aortofemoral bypasses [3,5,8,11,12,14,15,16,18]. Based on experimental and clinical studies, two different approaches have been proposed, each of which has its own advantages and drawbacks.…”
Section: Discussionmentioning
confidence: 99%